2019
DOI: 10.1177/1461444819864903
|View full text |Cite
|
Sign up to set email alerts
|

Tinder’s lesbian digital imaginary: Investigating (im)permeable boundaries of sexual identity on a popular dating app

Abstract: Dating apps have received rapid uptake, with Tinder as one of the most popular apps in the heterosexual market. However, little research has investigated the experiences of women seeking women (WSW) on this app. This article combines two interview studies of WSW in Australia, Canada, and the United Kingdom to investigate their self-presentations of sexual identity on Tinder. By configuring settings to “seeking women,” participants perceived they were entering a space conducive to finding WSW. However, men, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
0
30
0
2
Order By: Relevance
“…The past and current likelihood of using dating apps in people from sexual minorities was more than three times greater than that of heterosexual people, in line with existing evidence. As has already been shown, dating apps are a resource widely used by people from sexual minorities, especially those who have more difficulty expressing their sexuality and/or finding a partner [11][12][13].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The past and current likelihood of using dating apps in people from sexual minorities was more than three times greater than that of heterosexual people, in line with existing evidence. As has already been shown, dating apps are a resource widely used by people from sexual minorities, especially those who have more difficulty expressing their sexuality and/or finding a partner [11][12][13].…”
Section: Discussionmentioning
confidence: 92%
“…Sexual orientation also influences the use of these applications. Several studies have found greater use in people of sexual minorities than among heterosexuals [11,12]. Further, it has been emphasized that being able to contact and communicate online can be particularly useful for people of these minorities who have trouble expressing their sexuality and/or finding a partner [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is troublesome that women have to use their selfpresentations on a dating site for non-heterosexuals to fight off unwanted sexual attention from men. Unfortunately, it is not uncommon that men contact and harass non-heterosexual women on online dating sites, even when the women have set their settings to only show women and clearly signal their (homo)sexuality (Duguay, 2019;Ferris and Duguay, 2019). Men are not spared textual and visual sexual harassment on the present site.…”
Section: Sexual Harassmentmentioning
confidence: 85%
“…The taxonomy of research on different dimensions of digital visibility proposed in this article sheds light on the anteced ents of inequalities, polarization, and so cial change in digital media environments that can be described as an interplay of technological affordances and social / gen der norms. Applying this taxonomy to re search on women's digital visibility is only a first step that should be complemented by investigating further gender categories (nonbinary, trans) and their intersections with other social categorizations and char acteristics (e. g., sexual orientation; Ferris & Duguay, 2020). Further development of this approach can help to disentangle the causes and consequences of inequalities in digital visibility by identifying processes of replication, reinforcement, and resil ience.…”
Section: Discussionmentioning
confidence: 99%